Theoretical foundations of the formation of the philosophy of education - Sayganova, Veronika S.; Ren, Zheng (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article discusses the theoretical foundations of the formation of the philosophy of education. The problematic field of the philosophy of education is revealed. The formation of the philosophy of education was preceded by the development of philosophical anthropology, pedagogy, and some areas of psychology and sociology. The theoretical foundations of the formation of the philosophy of education are considered in the directions of postclassical philosophy, where holistic interpretations of a person, humanitarian knowledge, and the implementation of this knowledge in education were manifested. The main blocks of philosophical research are highlighted, in which the theoretical foundations of the philosophy of education are revealed. The conclusion is made that the formation of the philosophy of education took place within the framework of the analytical philosophical tradition, which determined the content directions and vectors of the further development of the philosophy of education.